2011
DOI: 10.1128/aem.05553-11
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Inactivation for Safe and Rapid Diagnostics of Infectious Samples

Abstract: The high risk associated with biological threat agents dictates that any suspicious sample be handled under strict surety and safety controls and processed under high-level containment in specialized laboratories. This study attempted to find a rapid, reliable, and simple method for the complete inactivation of a wide range of pathogens, including spores, vegetative bacteria, and viruses, while preserving microbial nucleic acid fragments suitable for PCRs and proteinaceous epitopes for detection by immunoassay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Review of previous photobiologic studies showed microbial inactivation results to be frequently impaired by lack of proper dosimetry or lacking controls that confounded results and prevented quantitative conclusions (reviewed in [25]). We took considerable effort in assuring that the viruses in this study were not inactivated by heat or direct germicidal UV radiation that could invalidate our photoianctivation experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of previous photobiologic studies showed microbial inactivation results to be frequently impaired by lack of proper dosimetry or lacking controls that confounded results and prevented quantitative conclusions (reviewed in [25]). We took considerable effort in assuring that the viruses in this study were not inactivated by heat or direct germicidal UV radiation that could invalidate our photoianctivation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The quencher, a 6‐carboxy‐tetramethyl‐rhodamine (TAMRA), was located at the 3′end. The sequences of primers and probes for the amplification of the 145 bp vaccinia virus specific and the 192 bp pixuna virus‐specific amplicon, as well as the optimal cycling conditions, have been presented as supplemental information in a previous publication (25). The rtPCR targeted the A27L gene of poxviruses, the rtRT‐PCR targeted the nsP1 gene of Alphaviruses.…”
mentioning
confidence: 99%
“…Alkaline glutaraldehyde. Adjust the sample to pH 8 by adding sufficient sodium bicarbonate (Sagripanti et al, 2011) from a prepared stock. (For example, a 0.3% w/v final concentration of NaHCO 3 may be a useful starting point.)…”
Section: Inactivation Of Vegetative Bacteria and Enveloped Virusesmentioning
confidence: 99%
“…Add household bleach to samples to a final bleach dilution of 1:10 to 1:100 v/v. Mix and incubate for 30 minutes (Sagripanti et al, 2011).…”
Section: Bacterial Spore Disinfectionmentioning
confidence: 99%
“…Ag alloy and Ag oxide have been used to create a layer in latex catheter which would lead to infection control during catherization . However, in a broader scene, Ag has been observed to prevent adhesion and growth of bacteria, E. coli and P. aeruginosa . Although, Ag salts may be directly used to coat the surface, nanosilver has recently gained enormous momentum toward the generation of an effective surface against microbes due to serious problem associated with metallic salts in terms of the leaching of the agent during use and hence leading to the toxicity of the tissue .…”
Section: Strategies For Developing Antimicrobial Catheter Surfacementioning
confidence: 99%